Translation Ideology in Rendering Compliment Responses in the Novel Bumi Manusia - Ilma Yullinda Rahmah; Mohammad Yahya; Siti Yuliah; Meita Kristia Namami (TRANSBAHASA, 2026)
Compliment response is an important pragmatic issue in literary translation because it reflects norms of politeness, humility, and interpersonal relationship management that are deeply rooted in culture. This study aims to analyze the translation ideology underlying the translation of compliment responses from Indonesian into English in Pramoedya Ananta Toer's novel Bumi Manusia. The data consist of 20 compliment responses identified purposively from the source text and their translations in the target text. This study uses a qualitative descriptive approach because the data consists of a linguistic unit, including words, phrases, clauses, or sentences expressing responses to compliments. The data were first analyzed by classifying the types of compliment responses based on Herbert’s taxonomy, then examining the ideological orientation based on Venuti’s concept reflected in the translation techniques used at the discourse-pragmatic level. The results indicate a strong tendency toward the foreignization ideology in translating compliment responses, reflected by the predominant use of literal translation techniques with minimal adjustments. In other words, the types of compliment responses in the source text are consistently maintained in the target text, in which translation ideology plays a significant role in maintaining the pragmatic interaction patterns of the source culture in literary translation. The implications of this study emphasize the importance of both pragmatic and ideological awareness in translating compliment responses, particularly in the context of postcolonial literary translation.